A Comparative Study of Translation Ideologies in Onomatopoeia Across Cultures in Story Weaver - Hardiyanti, Diana; Setiawan, Anjar; Setyowati, Lilis; Izzatuna, Nurul Farrah (Langkawi: Journal of The Association for Arabic and English, 2024)
This research compares the translation ideologies applied to onomatopoeia in level two children’s literature on the StoryWeaver website. Translators at Story Weaver often face a dilemma between preserving the original sound (onomatopoeia) or adapting it to the perception of children in the target culture. It aims to provide insights into effective translation techniques for onomatopoeia and to contribute to translation theory by examining the ideologies on cross-cultural understanding in children's literature. The study focuses on translation products, using linguistic and translation data, including techniques, methods, and ideologies. Data sources comprised documents and informants. The documents included nine children’s literature translated by The Story Weaver Community, The Asian Foundation, and the Badan Pengembangan dan Pembinaan Bahasa while informants were raters. Data collection involved document analysis and Focus Group Discussions (FGD). Data analysis employed domain analysis, taxonomy, component analysis, and cultural themes to identify, categorize, and understand how translation techniques and ideologies affect cultural understanding. The findings indicate that translators from The StoryWeaver Community and The Asian Foundation generally favor target language-oriented techniques (adaptation, established equivalent) with adaptation methods and domestication ideologies. In contrast, translators from Badan Pengembangan dan Pembinaan Bahasa (Agency for Language Development and Cultivation.) often employ source language-oriented techniques (Pure borrowing, naturalized borrowing., literal), use literal translation methods and foreignization ideologies. The study hopes to serve as a reference for translating onomatopoeia, offering valuable insights into how different translation techniques affect the translation ideologies outcomes.